ANALISIS HARGA SAHAM DAN VOLUME PERDAGANGAN SAHAM SEBELUM DAN SESUDAH STOCK SPLIT DI BURSA EFEK INDONESIA - Ahlul Ihsan Ramadhon, (2022)
This research is in the form of quantitative research that aims to analyze differences in stock prices and stock trading volumes before and after the stock split. The sample selection in this study was carried out using a full sampling method and obtained a sample of 31 companies from companies listed on the Indonesia Stock Exchange and had carried out stock split corporate actions during the 2018 until 2021 period. Hypothesis testing in this study used the SPSS version 28 program using the Wilcoxon Signed-Rank Test for both variables data that are not normally distributed. The results of the research are that there is no difference between stock prices before and after the stock split, while there is a difference between the stock trading volume before and after the stock split.